Inflammatory Breast Cancer: High Incidence of Detection of Mixed Human Cytomegalovirus Genotypes Associated with Disease Pathogenesis - Mohamed, Hossam Taha; El-Shinawi, Mohamed; Nouh, M. Akram; Bashtar, Abdel-Rahman; Elsayed, Elsayed Tarek; Schneider, Robert J.; Mohamed, Mona Mostafa (Frontiers in Oncology, 2014)
Inflammatory breast cancer (IBC) is highly metastatic, aggressive and fatal form of breast cancer. Patients presenting with IBC are characterized by a high number of axillary lymph node metastases. Recently, we found that IBC carcinoma tissues contain significantly higher levels of human cytomegalovirus (HCMV) DNA compared to other breast cancer tissues, that may regulate cell signaling pathways. In fact, HCMV pathogenesis and clinical outcome can be statistically associated with multiple HCMV genotypes within IBC. Thus, in the present study, we established the incidence and types of HCMV genotypes present in carcinoma tissues of infected non-IBC versus IBC patients. We also assessed the correlation between mixed detection of different HCMV genotypes and disease progression. Genotyping of HCMV in carcinoma tissues revealed that gB1 and gN1 were the most prevalent HCMV genotypes in both non-IBC and IBC patients with no significant difference between patients groups. IBC carcinoma tissues however, showed statistically significant higher incidence of detection of the gN-3b genotype compared to non-IBC patients. The incidence of mixed detection of different gB genotypes showed that gB1+gB3 was statistically significantly higher in IBC than non-IBC patients. Similarly, the incidence of mixed detection of different gN genotypes showed that gN-1+gN-3b and gN3+gN-4b/c were statistically significant higher in the carcinoma tissues of IBC than non- IBC. Mixed presence of HCMV different genotypes was found to be significantly correlated with the number of metastatic lymph nodes in non-IBC but not in IBC patients. In IBC, mixed detection of different HCMV genotypes significantly correlates with lymphovascular invasion and formation of dermal lymphatic emboli, which was not found in non-IBC patients.